U Have Integrity: A Gamified Approach to Academic Integrity (Canadian Perspectives on Academic Integrity, 2019)
In this article I discuss the development and initial implementation of a workshop using a gamified approach to academic integrity. The 50-minute workshop involved a scenario- based card came. The audience was university staff in Student and Enrolment Services, which included, but was not limited to the Registrar’s Office, Student Services, and Student Wellness.